Software Tools for Automation of Parallel Programming on the Basis of Algebra of Algorithms - Andon, F. I.; Doroshenko, A. E.; Beketov, A. G.; Iovchev, V. A.; Yatsenko, E. A. (Cybernetics and systems analysis, 2015)
The development of the algebra-algorithmic methodology and tools for automated design and generation of programs for graphics processing units is proposed. A particular feature of the proposed approach is the use of high-level specifications that are close to natural-language specifications and also the application of a method that ensures the syntactical correctness of algorithms and programs being designed. The approach was implemented in a toolkit destined for interactively designing algorithm schemes and generating programs. The use of this toolkit is illustrated by the development of a parallel program in the field of meteorology.